Khasiat Ekstrak Buah Markisa Kuning (P. Edulis Sims) sebagai Antiinflamasi Dilihat dari Jumlah Monosit pada Tikus Wistar Jantan (Rattus norvegicus) - Hardhika Oktarianda Fachri; Winny Adriatmoko; Pudji Astuti (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2018)
Yellow passion fruit contains carotenoids and polyphenols which are believed to be used as alternative treatments. Yellow passion fruit is thought to provide anti- inflammatory effects. The objective was to determine the efficacy of giving yellow passion fruit extract to inflammation seen from monocyte counts. This study used 12 male Wistar rats were divided into normal groups, treatment groups, and control groups. In the treatment group, yellow passion fruit extract was given 100% concentration. On the 1st, 3rd, and 7th day the blood edge of the rat was taken and the number of monocyte cell counts was performed. Based on the results of One Way Anova analysis there were differences in the number of monocyte cells between all groups. Yellow passion fruit extract (Passiflora edulis Sims) is efficacious as anti-inflammatory due to a decrease in the number of monocytes.